Spatial task context makes short-latency reaches prone to induced Roelofs illusion - Taghizadeh, Bahareh; Gail, Alexander (Frontiers in Human Neuroscience, 2014)
The perceptual localization of an object is often more prone to illusions than an immediate visuomotor action towards that object. The induced Roelofs effect (IRE) probes the illusory influence of task-irrelevant visual contextual stimuli on the processing of task-relevant visuospatial instructions during movement preparation. In the IRE, the position of a task-irrelevant visual object induces a shift in the localization of a visual target when subjects indicate the position of the target by verbal response, key-presses or delayed pointing to the target (‘perception’ tasks), but not when immediately pointing or reaching towards it without instructed delay (‘action’ tasks). This discrepancy was taken as evidence for the dual-visual-stream or perception-action hypothesis, but was later explained by a phasic distortion of the egocentric spatial reference frame which is centered on subjective straight-ahead and used for reach planning. Both explanations critically depend on delayed movements to explain the IRE for action tasks. Here we ask: first, if the IRE can be observed for short-latency reaches; second, if the IRE in fact depends on a distorted egocentric frame of reference. Human subjects were tested in new versions of the IRE task in which the reach goal had to be localized with respect to another object, i.e., in an allocentric reference frame. First, we found an IRE even for immediate reaches in our allocentric task, but not for an otherwise similar egocentric control task. Second, the IRE depended on the position of the task-irrelevant frame relative to the reference object, not relative to subjective straight-ahead. We conclude that the IRE for reaching does not mandatorily depend on prolonged response delays, nor does it depend on motor planning in an egocentric reference frame. Instead, allocentric encoding of a movement goal is sufficient to make immediate reaches susceptible to IRE, underlining the context dependence of visuomotor illusions.